Contextualising the social capital of Australian Aboriginal and non-Aboriginal men in prison - Lafferty, L.; Treloar, C.; Chambers, G.; Butler, Tony; Guthrie, J. (Pergamon Press, 2016)
© 2016Social capital is a valuable resource that has received little attention in the prison context. Differences in the construct and accessibility of bonding, bridging, and linking social capital exist for Aboriginal Australians in mainstream society, but were previously unexplored in prison. This study seeks to understand contextual differences of social capital for Australian Aboriginal and non-Aboriginal men in prison. Thirty male inmates participated in qualitative interviews across three New South Wales (NSW) correctional centres. Interviews were completed between November 2014 and March 2015. Experiences of bonding and linking social capital varied among Aboriginal and non-Aboriginal participants. Opportunities for bridging social capital were limited for all participants. There is greater scope for building bonding social capital among male inmates than either bridging or linking social capital. Bonding social capital, particularly among Aboriginal men in prison, should be utilised to promote health and other programs to inmates.